ANASTHETIC MANAGEMENT OF CIRCUMCISION IN A 4-YEAR - OLD CHILD WITH PULMONARY STENOSIS - A CASE REPORT - Dr. Nivedhitha R; Dr. Geetha J. (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
The largest category of human birth defects accounts for almost one percent of malformations among live birth abnormalities, including heart and vascular anomalies. 33 percent of children with chromosomal abnormalities have a congenital heart defect. Isolated pulmonary stenosis with an intact ventricular septum consists of 10 % of congenital heart defects, with further subdivision of valvular, supravalvular, and infravalvular lesions. Of these valves, pulmonary stenosis is the most common, about 80-90% of the reported cases. This case report discusses a 4-year-old child with tight phimosis and straining for micturition, posted for circumcision, on echocardiogram, follow-up of pulmonary stenosis was detected at birth.